Educação física escolar: concepções e princípios sobre inclusão escolar de professores da Rede Municipal de Fortaleza - Cunha, Raissa Forte Pires (2015)
In the present study aimed to analyze the concepts and principles of inclusive education that characterize the educational activities of physical education teachers who welcome students with sensory disabilities, physical and / or intellectual.It was based on sociointeractionist perspective, highlighting especially the contributions of Vygotsky about the importance of mediation. Other authors also substantiate this study such as City and Freitas (2002); Mittler (2003); Mantoan (2003); Aguiar and Duarte (2005); Rodrigues (2006); Figueiredo (2006; 2011); Ropoli et al. (2010); Mauerberg De Castro (2011). The qualitative methodology was characterized as a multiple case study. The study included two (2) Physical Education teachers from regular public education of Fortaleza, that have students with sensory disabilities, physical and / or intellectual in their classes. The data collection procedures consisted of applying interviews and observations of the classes of subjects on the basis of a constructed scale for this purpose. The results of this study showed that the barriers to learning and participation of students with disabilities in physical education classes are a constant practice of the teachers of this research. Regarding the discourse, the discourse of teachers indicated a discrepancy in their statements about the school inclusion, reflecting on their practices, as they do not favor the inclusion of students with disabilities. We conclude that is required greater investment in the formation of physical education teachers, so that they can use resources, materials and strategies for the inclusion of students with disabilities in physical education classes.